Determinants of the Gender Pay Gap in the Czech Republic and Selected European Countries - Savina Finardi (European Financial and Accounting Journal, 2022)
The goal of the article is to analyse determinants of the gender pay gap in selected European countries. For my analysis, I used different types of data published by Eurostat, OECD, the Czech Statistical Office and the Ministry of Labour and Social Affairs of the Czech Republic. Determinants have been estimated using multiple regression analysis in selected European countries including the Czech Republic. The article is also focused on the Czech Republic data on the gross average salary in private and public sectors according to gender and administrative regions. Results show that the maternity benefits and a complicated situation in the labour market, where full-time jobs are preferred, and moreover the parental allowances are strong drivers of the gender pay gap in the Czech Republic. This implies that the issue of the gender pay gap in the Czech Republic is rather structural, influenced by the social system and the labour market features. Future research should take into consideration the tax allowances as well (specific tax credits on children and a spouse).
Keywords: J31; J39; 650; Gender Pay Gap; Equal Pay; Czech Republic; EU; OECD